Assessing the relationships between problem representation, capabilities and task performance fraud risk assessment by Nigerian deposit money banks' fraud investigators - Odukoya, Olusoji Olumide (2021)
The purpose of the study is to investigate the mediating role of fraud-related problem representation on the relationship between knowledge, skills, mind-set and ethics capability constructs of fraud investigators and task-performance fraud risk assessments within Nigeria deposit money banks. Extensive literature in auditing, forensic accounting, banking and related fields was reviewed for thorough understanding of past, present and future trends in the study area. The research employed quantitative methodology. A total of 450 questionnaires were administered by simple random sampling on forensic accountants and bank examiners within CBN, NDIC and 20 deposit money banks, of which 338 questionnaires were returned, representing a 75% response rate. Current versions of PLS-SEM and IBM-SPSS were deployed for data cleaning, analyses and validation. Thirteen out of nineteen hypotheses were evaluated through PLS-SEM algorithm and bootstrapping, whilst Mann-Whitney U Test was deployed to evaluate six hypotheses related to differences in ranking between forensic accountants and bank examiners. Results provide verifiable supports for twelve of the hypothesised relationships and seven deviations from previous literature. Knowledge and skills capabilities and fraud-related problem representation were significantly positively related to task-performance fraud risk assessment. Furthermore, knowledge, skills, mind-set and ethics of fraud investigators were significantly positively related to fraud-related problem representation, indicating they are essential requirements for enhancing fraud risk assessment within banks. However, findings did not provide support for differences in ranking between groups, as forensic accountants were not found to possess significantly higher levels of knowledge, skills, mind-set, ethics and fraud-related problem representation than bank examiners. Consequently, as theory of planned behaviour prescribed, fraud investigators need to design appropriate procedures for risk assessment, especially when institutions is tainted by weak internal control and risk management structures. The study also recommends integration of forensic accountants and bank examiners as permanent fixtures for fraud prevention and detection.